2013
DOI: 10.1071/ah11122
|View full text |Cite
|
Sign up to set email alerts
|

Build it and they will come: outcomes from a successful cardiac rehabilitation program at an Aboriginal Medical Service

Abstract: Objective. Cardiovascular disease (CVD) is the leading disease burden in Aboriginal Australians, but culturally appropriate cardiac rehabilitation programs are lacking. We evaluated the uptake and effects on lifestyle, and cardiovascular risk factors, of cardiac rehabilitation at an Aboriginal Medical Service (AMS).Methods. The program involved weekly exercise and education sessions (through 'yarning') for Aboriginal people with or at risk of CVD. Participants' perceptions of the program and the impact on risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
131
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(138 citation statements)
references
References 15 publications
6
131
1
Order By: Relevance
“…Of these Eley et al (2010) detected improved outcomes for Study 1 but not Study 2 or for two subsequent iterations of the program. For eight interventions described in the study, observed improvements were statistically significant (O'Dea 1984; Lee et al 1994;Rowley et al 2001;d'Espaignet et al 2003;Nagel et al 2009;Eley et al 2010;Dimer et al 2013;Sun and Buys 2013). Two studies where statistical analyses were not conducted show positive directions of effects in health and wellbeing outcomes (Nel and Pashen 2003;Preuss and Brown 2006) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these Eley et al (2010) detected improved outcomes for Study 1 but not Study 2 or for two subsequent iterations of the program. For eight interventions described in the study, observed improvements were statistically significant (O'Dea 1984; Lee et al 1994;Rowley et al 2001;d'Espaignet et al 2003;Nagel et al 2009;Eley et al 2010;Dimer et al 2013;Sun and Buys 2013). Two studies where statistical analyses were not conducted show positive directions of effects in health and wellbeing outcomes (Nel and Pashen 2003;Preuss and Brown 2006) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Eley et al (2010) showed improved outcomes only for senior school boys in one of two described studies. The study related to physical activity with the most highly rated design (Dimer et al 2013) showed a range of significant clinical improvements. However, even this study only reported outcome data for a small proportion of those who commenced the program.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations